Matthieu est-il plus juif que Luc? - Oliver, Isaac W. 1980- (2017)
Ever since the days of Papias, Matthew has been cast as the Hebrew' or Jewish' gospel addressed primarily to Jewish Christians.' By contrast, the Christian tradition has ascribed the composition of the gospel of Luke and Acts to Luke, the Gentile Christian par excellence. If modern scholarship today largely recognizes the Jewish dimension of Matthew's gospel, including its affirmation of the Torah for Jewish followers of Jesus, the traditional view of Luke and Acts, which denies any real interest on the part of their author(s) in Torah praxis and Judaism, still reigns widely. The following article questions this longstanding dichotomy between Matthew and Luke by claiming that Luke and Acts are just as Jewish as Matthew as far as their respective affirmations of Torah practice for Jewish followers of Jesus are concerned.